2018
DOI: 10.1021/acs.molpharmaceut.8b00905
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Screen and Structural Analysis Identifies Bacterial Kinase Inhibitors which Act with β-Lactams To Inhibit Mycobacterial Growth

Abstract: New tools and concepts are needed to combat antimicrobial resistance. Actinomycetes and firmicutes share several eukaryotic-like ser/thr kinases (eSTK) that offer antibiotic development opportunities, including PknB, an essential mycobacterial eSTK. Despite successful development of potent biochemical PknB inhibitors by many groups, clinically useful microbiologic activity has been elusive. Additionally, PknB kinetics are not fully described, nor are structures with specific inhibitors available to inform inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 80 publications
1
47
0
1
Order By: Relevance
“…Their in silico structural docking revealed a family of imidazopyridine aminofurazan lead compounds with high binding affinity toward PknB. Intriguingly, and consistent with the known role of PknB in cell wall homeostasis, these inhibitors were able to significantly potentiate the effect of b-lactams in several types of mycobacteria and in the related Nocardia asteroides [236]. This synergistic concept has also been reported for kinase inhibitors of the nonessential L. monocytogenes PrkA and S. aureus Stk1 Hanks kinases [219,223,[237][238][239][240].…”
Section: Drugging Bacterial Kinasessupporting
confidence: 63%
See 1 more Smart Citation
“…Their in silico structural docking revealed a family of imidazopyridine aminofurazan lead compounds with high binding affinity toward PknB. Intriguingly, and consistent with the known role of PknB in cell wall homeostasis, these inhibitors were able to significantly potentiate the effect of b-lactams in several types of mycobacteria and in the related Nocardia asteroides [236]. This synergistic concept has also been reported for kinase inhibitors of the nonessential L. monocytogenes PrkA and S. aureus Stk1 Hanks kinases [219,223,[237][238][239][240].…”
Section: Drugging Bacterial Kinasessupporting
confidence: 63%
“…Another approach to identify kinase inhibitors is by in silico modeling. Wlodarchak et al [236] exploited the general structural similarity of bacterial and human Ser/ Thr kinases to identify PknB inhibitors by in silico screening of a human kinase inhibitor collection. Their in silico structural docking revealed a family of imidazopyridine aminofurazan lead compounds with high binding affinity toward PknB.…”
Section: Drugging Bacterial Kinasesmentioning
confidence: 99%
“…Analysis of the induced-fit docking poses of NU-6027 in PknB showed that the functional residues, such as Glu93 and Val95, are not involved in hydrogen bond formation with NU-6027. Previously, it has been shown that an inhibitor, G93, forms a hydrogen bond with residues such as Glu59, Lys40, and Asp156 (32). However, these residues are not involved in hydrogen bond formation in the predicted PknB:NU-6027 induced-fit docked poses (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…The kinase domain in 2PZI is reported with the DFG loop of the kinase domain in the "in" conformation (31); the information on the conformational state of the kinase domain in 5U94 (32) is not explicitly available. Superimposition of the kinase domain from different crystal structures of ligand-bound PknB complexes (1MRU, 1O6Y, and 2FUM) onto the kinase domain of PknB in 5U94 suggested that the DFG loop in the latter is in the "in" conformation (29,30,32,75). This pairwise superimposition was performed using the Protein Structure Alignment module in Maestro, version 11.01.011 (Schrodinger LLC).…”
Section: Methodsmentioning
confidence: 99%
“…Deletion or inhibition of PknB orthologues in Gram-positive bacteria can lead to increased susceptibility to β-lactam antibiotics [34][35][36], and meropenem has been shown to potentiate the activity of a PknB inhibitor 2-fold in auxotrophic M. tuberculosis [37]. Though carbapenems have been used to treat MDR-TB, cephalosporins and penicillins are generally not active against M. tuberculosis at clinically relevant concentrations.…”
Section: Increased Antibiotic Susceptibility In the Setting Of Pkna Amentioning
confidence: 99%